Роль китайского языка и культуры в повышении уровня межкультурной коммуникации между Беларусью и Китаем - Симирская, А. Н. (БНТУ, 2024)
This article discusses the main aspects of intercultural cooperation and communication between China and Belarus. The influence of Chinese language and culture on the process of intercultural communication between Belarus and China was revealed, and the role of Chinese language and culture in increasing the level of intercultural communication between the two countries was analyzed.